Collaborative Tourism Reconstruction Of The Bay Area In Palu City Following The 2018 Earthquake And Tsunami Disaster - Idham, Idham; Budiyanto, Budiyanto; Fadjrih Asik, Nur; Ilham, Ilham (International Journal of Educational Research & Social Sciences, 2022)
Palu Bay, which is developed as a tourism area, is in the ring of fire with a history of repeated disasters. This tourism was able to increase tourist visits to the city of Palu. However, the 2018 earthquake and tsunami resulted in a decrease in tourist visits to the city of Palu. In addition to determining the interaction patterns of the Palu city population, this study tries to pinpoint the key factors the government used to transform Palu Bay into a popular tourist destination. This is accomplished by identifying the key factors that make Palu Bay a popular tourist destination and figuring out how to boost tourism there in the wake of the 2018 earthquake and tsunami disaster. Schutz analysis was employed with post-positivist paradigm and transcendental phenomenology approach. Triangulation was used to collect data, while content analysis was used to process it.Key factors used by the local government of Palu City in developing Palu Bay as a tourism area included: 1. The potential of Palu Bay's natural resources with its natural beauty and unique five-dimensional city (sea, bay, valley, mountain and river); 2. Strategic location on the coast of Palu city with easy access for tourists, 3. Market share of domestic and international tourists; 4. Of the nine existing sub-sectors, Palu Bay has the potential to become the mainstay sector of the city of Palu to support the regional economy because the agricultural, mining, fisheries, industrial, housing and financial sectors lack the potential to be the mainstay sector. The development of tourism in the Palu Bay area is carried out by prioritizing disaster emergency mitigation and response with proper governance and principles of Good Corporate Governance (GCG). Collaborative Multidimensional reconstruction of the private sector, local communities and local governments (triple BCG) as well as patterns of disaster mitigation and emergency response to stimulate tourism in the Palu bay area affected by the 2018 earthquake and tsunami.